IMPROVING IPS LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING (PBL) MODELS IN CLASS V STUDENTS OF SD NEGERI NO 126 BORONG DISTRICT HERLANG, BULUKUMBA DISTRICT - Nur Afni; Abdul Wahid (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research is a Classroom Action Research (PTK) which aims to determine the increase in social studies learning outcomes through the Problem Based Learning (PBL) Model for fifth grade students at SD Negeri No. 126 Borong sub-district of Herlang, Bulukumba Regency. This research was carried out in two cycles where each cycle consisted of 4 meetings with 22 research subjects, namely fifth grade students at SD Negeri No. 126 Wholesale Subdistrict Herlang, Bulukumba Regency. Data collection using observation sheet instruments to see the activities of teachers and students as well as tests to determine student learning outcomes.The results showed that there was an increase in the average value of students and student learning completeness. The average value in the first cycle was 66.14 and in the second cycle it increased to 76.59. students' learning completeness in cycle I was 25% and in cycle II it increased to 90%.